Lexical incompatability as a means of creating illogical phrases in fiction texts - E A Yashina (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2011)
In the article under discussion the ways of creating illogical word combinations by means of using the lexical units aimed to create semantic-logical incongruity in fiction texts are analyzed. The use of lexical means causing incompatibility in fiction texts are illustrated in the classical literature quotations.